ETIKA KRISTEN DALAM PENGEMBANGAN BISNIS BERKELANJUTAN BERBASIS ECO-FRIENDLY - Saleleubaja, Junardi; Sinaga, Davin Anugrah; Saleleubaja, Musliadi Kumar; Nelson Hasibuan (TEOLOGIS, RELEVAN, APLIKATIF, CENDIKIA, KONTEKSTUAL, 2025)
This article aims to analyze the role of Christian ethics in the development of sustainable business, focusing on how Christian moral principles can be applied in the business context to create practices that not only prioritize profit but also contribute to social welfare and environmental sustainability. The method used in this research is qualitative descriptive with a library research approach. The researcher gathers and analyzes various literature related to Christian ethics, business sustainability, and corporate social responsibility. The results of the study indicate that Christian ethics, through principles such as love, justice, and integrity, can serve as a foundation for building sustainable businesses. Additionally, the application of Christian ethics in business can assist companies in balancing economic goals with social and ecological responsibilities, which in turn can enhance the company’s reputation and provide positive impacts on society and the environment. This research suggests that companies should pay more attention to Christian moral values in every business decision to achieve long-term sustainability in a more responsible manner.